Partial Validation of Ultra Performance Liquid Chromatography Method for Quantification of Isoniazid-Pyrazinamide in Human Samples - Vycke Yunivita; Triana Nurul Meirina; Atu Purnama Dewi; Harold Eka Atmaja; Rovina Ruslami (Chemistry Department, The University of Brawijaya, 2021)
Isoniazid (INH) and pyrazinamide (PZA) are first-line drugs in the treatment of meningitis of tuberculosis, in addition to rifampicin. The use of these drugs will determine the success of therapy to kill Mycobacterium tuberculosis in brain tissue that is difficult to penetrate by other drugs. Therefore, it is necessary to conduct research and monitor the use of this drug in plasma and cerebrospinal fluid (CSF) patients with TBM. This study aimed to determine the method of analysis of INH and PZA using Ultra Performance Liquid Chromatography Ultra Violet (UPLC-UV). The samples were taken from TBM patients who taken INH-PZA and others besides TBM patients who did not take INH-PZA. The analytic method carried out includes a comparison of the results of the analysis method for measuring levels of standard INH-PZA and INH-PZA in plasma and CSF samples. Analysis of INH-PZA in plasma and CSF can be performed using UPLC with UV detector, at least 100 uL plasma or CSF samples volume, with reproducible and accurate results.